INVERTED METAMORPHIC MULTIJUNCTION SOLAR CELL WITH TWO METAMORPHIC LAYERS AND HOMOJUNCTION TOP CELL (2016)
A multijunction solar cell includes an upper first solar subcell having a first band gap, a second solar subcell having a second band gap smaller than the first band gap, and a first graded interlayer composed of (InxGa1-x)yAl1-yAs adjacent to the second solar subcell. The first graded interlayer has a third band gap greater than the second band gap subject to the constraints of having the in-plane lattice parameter greater or equal to that of the second subcell and less than or equal to that of the third subcell, wherein 0<x<1 and 0<y<1, and x and y are selected such that the band gap of the first graded interlayer remains constant throughout its thickness at 1.5 eV. A third solar subcell is adjacent to the first graded interlayer and has a fourth band gap smaller than the second band gap such that the third subcell is lattice mismatched with respect to the second subcell. A second graded interlayer composed of (InxGa1-x)yAl1-yAs is adjacent to the third solar subcell and has a fifth band gap greater than the fourth band gap subject to the constraints of having the in-plane lattice parameter greater or equal to that of the third subcell and less than or equal to that of the bottom fourth subcell, wherein 0<x<1 and 0<y<1, and x and y are selected such that the band gap of the second graded interlayer remains constant throughout its thickness at 1.1 eV. A lower fourth solar subcell is adjacent to the second graded interlayer and has a sixth band gap smaller than the fourth band gap.